Range expansion of the small spruce bark beetle Ips amitinus: a newcomer in northern Europe. (13th March 2019) - Økland, Bjørn; Flø, Daniel; Schroeder, Martin; Zach, Peter; Cocos, Dragos; Martikainen, Petri; Siitonen, Juha; Mandelshtam, Michail Y.; Musolin, Dmitry L.; Neuvonen, Seppo; Vakula, Jozef; Nikolov, Christo; et al.
Abstract: Ips amitinus arrived in Northern Europe at the beginning of 1900s, although its recent expansions to the northernmost conifers have been rapid. Analyses of recent records, MaxEnt models and regional population size estimates are used to discuss its peculiar range shifts and potential as a forest pest in Northern Europe. Ips amitinus was probably absent in northern glacial refugia for Norway spruce in the Russian plain and northward expansions from its glacial refugia in the Central European mountains may have been slowed down by: (i) ecological barriers of post‐glacial dry plains and bogs in Central Europe; (ii) heavy utilization of conifers; and (iii) Allee effects as a result of fragmented forests and an unfavourable climate for a cold‐adapted species in the continental lowlands. MaxEnt models predict that I. amitinus may become widespread in the Northern European forests, whereas its populations in the southernmost mountain ranges of Europe may decline in the future. The population levels of I. amitinus in recently invaded northern areas are still lower than those in core areas of Central Europe, although the population development in Central Europe indicates that future bark beetle outbreak periods may boost the I. amitinus populations in Northern Europe as well. Abstract : Maxent models predict strong populations in north and decline in south. The small spruce bark beetle has conquered most of Northern Europe during few decades. Initial expansions from glacial refugia in the Central European Mountains may have been slowed by low host tree density and unfavourable climate in the Central European lowlands.